Yeast-based attract-and-kill strategies for Drosophila suzukii management without disrupting honey bee activity. - Claire Duménil; Urban Spitaler; Guillermo Rehermann; Flavia Bianchi; Riccardo Favaro; Irene Castellan; Silvia Schmidt; Daniela Eisenstecken; Paul G Becher; Sergio Angeli (PLoS ONE)
Attract-and-kill strategies are effective, sustainable pest control methods. Formulations combining the insecticide spinosad, at a lower dose than conventional methods, with the Drosophila-associated yeast Hanseniaspora uvarum have shown promising results. Recently, Saccharomycopsis vini was identified as the most attractive yeast for ovipositing females. In this study, the potential of S. vini for use in attract-and-kill formulations against D. suzukii was evaluated alongside H. uvarum. Behavioural assays demonstrated that D. suzukii preferred S. vini when both yeasts are simultaneously present in a close range setting but was attracted to both in long range attraction assays. In efficacy assays, S. vini and H. uvarum were equally efficient at reducing oviposition and increasing mortality in formulation with spinosad. Offering yeast formulations at the foraging sites of trained honey bees did not stimulate more feeding when compared to sugar syrup. The characterisation of the organic volatile compounds released from the cultures demonstrated that S. vini and H. uvarum were composed of overlapping as well as distinct chemicals. The antennally active compounds ethyl acetate and ethyl propanoate were abundant in the more attractive S. vini and H. uvarum, while the compounds 3-methyl-1-butanol and 2-methylthiolan-3-one were more abundant in the less attractive S. cerevisiae. These chemicals may be further studied as possible attractants or repellents for D. suzukii. We propose S. vini as a new yeast with potential for use in integrated pest management, with a distinctive volatile profile while maintaining a similar efficacy compared to H. uvarum against D. suzukii. Neither H. uvarum nor S. vini stimulated honey bee foraging behaviour, suggesting that both yeast-based attract-and-kill formulations pose a low non-target risk to honey bees.